Triple – negative essential thrombocythemia in a child: A diagnostic challenge - Neha Goel; Deepak Kumar Jha; Sanghamitra Ray; Sumit Mehndiratta; Nidhi Chopra; Amitabh Singh (Pediatric Hematology Oncology Journal, 2025)
Background: Essential thrombocythemia (ET) is a well-defined entity that is characterized by the presence of splenomegaly, uncontrolled hematopoiesis, and is independent of control of growth factors. The annual incidence of ET in children has been estimated to be around 0.004–0.11 per 100,000 children aged between 0 and 16 years of age. Case report: A 10-year-old girl child presented with hemetemesis and was found to have extreme thrombocytosis. There was no significant family history, and her parents' hemogram was within normal limits. The child was diagnosed as a case of 'triple negative' (JAK2-V617F, CALR and MPL mutation negative) essential thrombocythemia on whole exome sequencing. Since the child was asymptomatic, no treatment was initiated. The child has been followed up every two weeks for up to six months, and continued to have asymptomatic thrombocytosis. Conclusion: The case increases awareness amongst pediatric hematologists regarding this rare entity in childhood. This case also reemphasizes the importance of detailed work up in order to reach an accurate diagnosis.